The impact of wealth on job exit rates of elderly workers - Hans G. Bloemen (Institute for the Study of Labor (IZA), 2006)
In the literature theoretical models have appeared that predict a positive impact of the level of individual wealth on the job exit probability. Empirically this prediction is most likely to be relevant for elderly workers who have been able to accumulate wealth throughout their working life and whose residual working life is relatively short. In the Netherlands, as in other European countries, there is a tendency of introducing more individual choice options in pension schemes. It is likely that the individual level of wealth will become an increasingly important factor in the retirement decision. Therefore it is interesting to know whether individuals with a different financial situation make different job exit decisions, given other factors. Empirical analysis of job exit behaviour of elderly workers so far has concentrated on properties of the pension system and the health situation. For a sample of elderly male workers in the Netherlands in the period 1995 through 2001, we analyse the impact of wealth, savings, and debt position on job exit rates. We find evidence for a positive effect of wealth on the probability to retire (early).
Keywords: J26; D91; 330; retirement; life cycle models; saving; Altersgrenze; Vermögen; Ältere Arbeitskräfte; Sparen; Lebenszyklus; Theorie